2018
DOI: 10.1038/s41388-018-0414-x
|View full text |Cite
|
Sign up to set email alerts
|

KDM8/JMJD5 as a dual coactivator of AR and PKM2 integrates AR/EZH2 network and tumor metabolism in CRPC

Abstract: During the evolution into castration or therapy resistance, prostate cancer cells reprogram the androgen responses to cope with the diminishing level of androgens, and undergo metabolic adaption to the nutritionally deprived and hypoxia conditions. AR (androgen receptor) and PKM2 (pyruvate kinase M2) have key roles in these processes. We report in this study, KDM8/JMJD5, a histone lysine demethylase/dioxygnase, exhibits a novel property as a dual coactivator of AR and PKM2 and as such, it is a potent inducer o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
67
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 85 publications
(70 citation statements)
references
References 60 publications
3
67
0
Order By: Relevance
“…PKM2 deacetylation abolishes its nuclear protein kinase and transcription coactivator activities, leading to suppression of its nuclear oncogenic function and consequent tumor suppression and metastasis inhibition. KDM8, a histone lysine demethylase, binds directly to the interface area of PKM2 subunits, retarding PKM2 tetramer formation and promoting its nuclear translocation, where the KDM8/PKM2 complex acts as a coactivator of HIF-1α to induce the expression of glycolytic genes [ 64 , 65 ]. The data suggest that PKM2 may enter the nucleus as a monomer.…”
Section: Nuclear Localization Of Pkm2mentioning
confidence: 99%
“…PKM2 deacetylation abolishes its nuclear protein kinase and transcription coactivator activities, leading to suppression of its nuclear oncogenic function and consequent tumor suppression and metastasis inhibition. KDM8, a histone lysine demethylase, binds directly to the interface area of PKM2 subunits, retarding PKM2 tetramer formation and promoting its nuclear translocation, where the KDM8/PKM2 complex acts as a coactivator of HIF-1α to induce the expression of glycolytic genes [ 64 , 65 ]. The data suggest that PKM2 may enter the nucleus as a monomer.…”
Section: Nuclear Localization Of Pkm2mentioning
confidence: 99%
“…Indeed, a number of E2F targets including TOP2A, BIRC5/survivin, and ANCCA/ATAD2 are strongly downregulated by the combination treatment. Interestingly, ANCCA/ATAD2 is a critical coactivator of E2Fs and AR, and is also a direct target of AR and E2Fs (44,47,48). We previously demonstrated that ANCCA/ATAD2 activates the expression of TOP2A and BIRC5 (44,49).…”
Section: Discussionmentioning
confidence: 98%
“…For example, pyruvate generated from glycolysis is the main substrate for acetyl-CoA, a central metabolite coordinating the activity of the histone acetyltransferase (HAT) enzymes. Treatment-induced NEPC tumours exhibit elevated expression of the histone lysine demethylase KDM8, which functions to reprogram metabolism toward aerobic glycolysis (Wang et al 2019). Moreover, MYCN, which is implicated in neuroendocrine lineage reprogramming, increases mitochondrial export of acetyl groups and upregulates the HAT GCN5 leading to elevated histone acetylation and DNA accessibility (Knoepfler et al 2006).…”
Section: Interplay Between the Epigenetic Landscape And Metabolismmentioning
confidence: 99%